STUDY REGARDING THE DEVELOPMENT OF SKILL THROUGH SOME MEANS CHARACTERISTIC OF THE FOOTBALL GAME - Tatarcan Cătălin-Andrei (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
This study was based on the method of the experiment applied on two groups of football players, between 10 and 12-years-old. Both groups underwent some tests of skill measurement. The children in the first group, the experimental group, have done, during the trainings, different technical elements and procedures of skill development for two months. The final tests demonstrated an improvement of this motor ability compared to the children in the second group.